Sustainable hydrogen production: Technological advancements and economic analysis. (30th October 2022) - Ahmed, Shams Forruque; Mofijur, M.; Nuzhat, Samiha; Rafa, Nazifa; Musharrat, Afla; Lam, Su Shiung; Boretti, Alberto
Abstract: Hydrogen (H2 ) is pivotal to phasing out fossil fuel-based energy systems. It can be produced from different sources and using different technologies. Very few studies comprehensively discuss all available state-of-the-art technologies for H2 production, the challenges facing each process, and their economic feasibility and sustainability. The current study thus addresses these gaps to effectively direct future research towards improving H2 production techniques. Many conventional methods contribute to large greenhouse gas footprints, with high production costs and low efficiency. Steam methane reforming and coal gasification dominate the supply side of H2, due to their low production costs (<3.50/kg). Water-splitting offers one of the most environmentally benign production methods when integrated with renewable energy sources. However, it is considerably expensive and ridden with the flaw of production of harmful by-products that affect efficiency. Fossil fuel processing technologies remain one of the most efficient forms of H2 production sources, with yields exceeding 80% and reaching up to 100%, with the lowest cost despite their high reliance on expensive catalysts. Whereas solar-driven power systems cost slightly less than 10 kg −1, coal gasification and steam reforming cost below 3.05 kg −1 . Future research thus needs to be directed towards cost reduction of renewable energy-based H2 production systems, as well as in their decarbonization and designing more robust H2 storage systems that are compatible with long-distance distribution networks with adequate fuelling stations. Highlights: H2 production technologies, their economic feasibility and sustainability are reviewed. Low-cost steam methane reforming and coal gasification dominate the supply side of H2 . Water-splitting coupled with renewable sources offers one of the most eco-friendly methods. Future research should focus on decarbonizing and lowering renewable H2 production cost.